Rostros entre motivos vegetales. ¿Una travesura de miniaturistas? - Suárez González, Ana; Galván Freile, Fernando (Estudios humanísticos. Geografía, historia y arte, 1995)
Among the decorative motives of some of the original manuscripts of Saint Isidoro of Leon, written around 1200, a sequence of hidden faces can be found. This essay contains a brief study and catalogue of the main ornaments which show this peculiar motive.